Of Platonism and Phenomenology - Montserrat Molas, Josep (Differenz. Revista internacional de estudios heideggerianos y sus derivas contemporáneas, 2017)
After discussing the general situation of the Platonic studies and after some of the ruptures ocurred in the battles for Plato’s interpretation, the paper shows some of the latest developments of the research carried out by the research group “Eidos: platonisme i modernitat”. In connection with the Platonic phenomenology of Jan Patocka, is shown the intimate connection between Platonism, phenomenology and theater in the work of the Czech philosopher, as well as his disciple Vaclav Havel. It presents now only a preliminary development that will focus later on a reflection on the drama of Platonic dialogue.